UJI FITOKIMIA, TOKSISITAS DAN AKTIVITAS ANTIBAKTERI TERHADAP EKSTRAK ETANOL DAUN RAMBUSA (Passiflora foetida L.) TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Noviyanti Y; Subur P Pasaribu; Daniel T (JURNAL KIMIA MULAWARMAN, 2014)
Phytochemical tests were conducted, brine shrimp lethality test / BSLT and antibacterial activity test of the coarse extract and fractions from the Rambusa leaves (Passiflora foetida L.) derived from Samarinda, East Kalimantan. Rambusa leaf samples (Passifloa foetida L.) was extracted by ethanol, then concentrated using rotary evaporator. Then fractionated by using n-hexane and ethyl acetate solvent. According the test results, phytochemical compounds of secondary metabolites has contained alkaloids and steroidal compounds, triterpenoids. Within the antibacterial activity test using Staphylococcus aureus (Positive gram) and Escherichia coli (Negative Gram) using the discs method. This test using concentration in 1%, 5%, 10%, 15%, 20% resulted that the most active fraction is the fraction of n-hexane with minimum inhibitory rate was 1% and brine shrimp lethality test within concentration in 1000; 500; 250; 125; 62.5; 31.25; 15.625; 7,8125 ppm showing larval lethality of Artemia salina (L.) using SAS probit analysis to determine the value of Lethal Concentration 50% (LC 50 ). This test resulted that the most active fraction is the fraction of n-hexane with 133.7473 ppm of LC 50 values .Keywords : Passiflora foetida L. , phytochemical test , test antibacterial activity , bacterial and LC 50